Influence of paternal preconception exposures on their offspring: through epigenetics to phenotype - Day, Jonathan (Am J Stem Cells, 2016)
Historically, research into congenital defects has focused on maternal impacts on the fetal genome during gestation and prenatal periods. However, recent findings have sparked interest in epigenetic alterations of paternal genomes and its effects on offspring. This emergent field focuses on how environmental influences can epigenetically alter gene expression and ultimately change the phenotype and behavior of progeny. There are three primary mechanisms implicated in these changes: DNA methylation, histone modification, and miRNA expression. This paper provides a summary and subsequent review of past research, which highlights the significant impact of environmental factors on paternal germ cells during the lifetime of an individual as well as those of future generations. These findings support the existence of transgenerational epigenetic inheritance of paternal experiences. Specifically, we explore epidemiological and laboratory studies that demonstrate possible links between birth defects and paternal age, environmental factors, and alcohol consumption. Ultimately, our review highlights the clinical importance of these factors as well as the necessity for future research in the field.